First-line erlotinib versus gemcitabine/cisplatin in patients with advancedEGFRmutation-positive non-small-cell lung cancer: analyses from the phase III, randomized, open-label, ENSURE study - Wu, Y.L.; Zhou, C.; Liam, Chong Kin; Wu, G.; Liu, X.; Zhong, Z.; Lu, S.; Cheng, Y.; Han, B.; Chen, L.; Huang, C.; Qin, S.; et al. (Elsevier, 2015)
Background: The phase III, randomized, open-label ENSURE study (NCT01342965) evaluated first-line erlotinib versus gemcitabine/cisplatin (GP) in patients from China, Malaysia and the Philippines with epidermal growth factor receptor (EGFR) mutation-positive non-small-cell lung cancer (NSCLC). Patients and methods: Patients ≥18 years old with histologically/cytologically confirmed stage IIIB/IV EGFR mutation-positive NSCLC and Eastern Cooperative Oncology Group performance status 0-2 were randomized 1:1 to receive erlotinib (oral; 150 mg once daily until progression/unacceptable toxicity) or GP [G 1250 mg/m2 i.v. days 1 and 8 (3-weekly cycle); P 75 mg/m2 i.v. day 1, (3-weekly cycle) for up to four cycles]. Primary end point: investigator-assessed progression-free survival (PFS). Other end points include objective response rate (ORR), overall survival (OS), and safety. Results: A total of 217 patients were randomized: 110 to erlotinib and 107 to GP. Investigator-assessed median PFS was 11.0 months versus 5.5 months, erlotinib versus GP, respectively [hazard ratio (HR), 0.34, 95% confidence interval (CI) 0.22-0.51; log-rank P < 0.0001]. Independent Review Committee-assessed median PFS was consistent (HR, 0.42). Median OS was 26.3 versus 25.5 months, erlotinib versus GP, respectively (HR, 0.91, 95% CI 0.63-1.31; log-rank P = .607). ORR was 62.7% for erlotinib and 33.6% for GP. Treatment-related serious adverse events (AEs) occurred in 2.7% versus 10.6% of erlotinib and GP patients, respectively. The most common grade ≥3 AEs were rash (6.4%) with erlotinib, and neutropenia (25.0%), leukopenia (14.4%), and anemia (12.5%) with GP. Conclusion: These analyses demonstrate that first-line erlotinib provides a statistically significant improvement in PFS versus GP in Asian patients with EGFR mutation-positive NSCLC (NCT01342965).